Origin of complex behaviour of spatially discordant alternans in a transgenic rabbit model of type 2 long QT syndrome - Ziv, Ohad (Blackwell Science Inc, 2009)
Enhanced dispersion of repolarization has been proposed as an important mechanism in long QT related arrhythmias. Dispersion can be dynamic and can be augmented with the occurrence of spatially out-of-phase action potential duration (APD) alternans (discordant alternans; DA). We investigated the role of tissue heterogeneity in generating DA using a novel transgenic rabbit model of type 2 long QT syndrome (LQT2). Littermate control (LMC) and LQT2 rabbit hearts (n= 5 for each) were retrogradely perfused and action potentials were mapped from the epicardial surface using di-4-ANEPPS and a high speed CMOS camera. Spatial dispersion (ΔAPD and Δslope of APD restitution) were both increased in LQT2 compared to LMC (ΔAPD: 34 ± 7 ms vs. 23 ± 6 ms; Δslope:1.14 ± 0.23 vs. 0.59 ± 0.19). Onset of DA under a ramp stimulation protocol was seen at longer pacing cycle length (CL) in LQT2 compared to LMC hearts (206 ± 24 ms vs. 156 ± 5 ms). Nodal lines between regions with APD alternans out of phase from each other were correlated with conduction velocity (CV) alternation in LMC but not in LQT2 hearts. In LQT2 hearts, larger APD dispersion was associated with onset of DA at longer pacing CL. At shorter CLs, closer to ventricular fibrillation induction (VF), nodal lines in LQT2 (n= 2 out of 5) showed persistent complex beat-to-beat changes in nodal line formation of DA associated with competing contribution from CV restitution and tissue spatial heterogeneity, increasing vulnerability to conduction block. In conclusion, tissue heterogeneity plays a significant role in providing substrate for ventricular arrhythmia in LQT2 rabbits by facilitating DA onset and contributing to unstable nodal lines prone to reentry formation.